Mid-crustal storage and crystallization of Eyjafjallajökull ankaramites, South Iceland - Nikkola, Paavo; Bali, Enikő; Kahl, Maren; Meer, Quinten H. A. van der; Rämö, O. T.; Guðmundur H. Guðfinnsson; Þorvaldur Þórðarson (Jökull, 2019)
Our understanding of the long-term intrusive and eruptive behaviour of volcanic systems is hampered by a relatively short period of direct observation. To probe the conditions of crustal magma storage below South Iceland, we have analysed compositions of minerals, mineral zoning patterns, and melt inclusions from two Eyjafjallajokull ankaramites located at Brattaskjol and Hvammsmuli. These two units are rich in compositionally diverse macrocrysts, including the most magnesian olivine (Fo(88)(-)(90)) and clinopyroxene (Mg#(cpx)( )89.8) known from Eyjafjallajokull. Olivine-hosted spinel inclusions have high Cr# (spl)(52-80) and TiO2 (1-3 wt%) and low Al2O3 (8-22 wt%) compared to typical Icelandic chromian spinel. The spinel-olivine oxybarometer implies a moderate oxygen fugacity of Delta logFMQ 0-0.5 at the time of crystallization, and clinopyroxene-liquid thermobarometry crystallization at mid-crustal pressures (1.7-4.2 kbar, 3.0+1.4 kbar on average) at 1120-1195 degrees C. Liquid-only thermometry for melt inclusions with Mg#(melt) 56.1-68.5 and olivine-liquid thermometry for olivine macrocrysts with Fo(80.7-88.9) yield crystallization temperatures of 1155-1222 degrees C and 1136-1213 degrees C, respectively. Diffusion modelling of compositional zonations in the Brattaskjol olivine grains imply that the Brattaskjol macrocusts were mobilized and transported to the surface from their mid-crustal storage within a few weeks (at most in 9-37 days). Trends in clinopyroxene macrocryst compositions and the scarcity of plagioclase indicate that the mid-crustal cotectic assemblage was olivine and clinopyroxene, with plagioclase joining the fractionating mineral assemblage later. In all, the crystal cargoes in the Brattaskjol and Hvammsmtili ankaramites are composed of agitated wehrlitic or plagioclase wehrlitic crystal mushes that crystallized over a large temperature interval at mid-crustal depths.